New Distributional Records with a Prelimanary Checklist of Gyrinidae (Order: Coleoptera) of Maharashtra, India - Takawane, Pallavi; Deb, Rita; Pokale, Sandeep; Subramanian, K A (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present study is based on some collections of aquatic beetles of family Gyrinidae Latreille, 1810 from different locations of Maharashtra. This study contributes new and updated records of family Gyrinidae from the state of Mahrashtra. 12 species of the family have been reported so far from Maharashtra. The present study reports the presence of Dineutus (Cyclous) spinosus (Fabricius, 1781) and Gyrinus convexiusculus Macleay, 1871 from Maharashtra for the first time, the range of the genus Gyrinus Geoffrey, 1762 to one more state of India, Maharashtra has also been extended.